Gerotranscendence and active aging: the lived experience. - Raeesi Dehkordi, Fatemeh; Eslami, Ahmad Ali; Zamani Alavijeh, Fereshteh; Matlabi, Hossein (Journal of Religion, Spirituality & Aging, 2021)
Active aging is a comprehensive and subjective concept that depends on an individuals' personal experiences. The theory of gerotranscendence focuses on seniors and the aging process. This process would be of great value in dealing with the challenges that come in that period of life. The authors conducted this study to explore the lived experience of gerotranscendence and active aging among seniors. Following a directed content analysis procedure, we conduct semi-structured individual interviews with 39 community-dwelling seniors from the age of 60 including both genders living in Isfahan selected by purposeful sampling. Data collection and analysis were concurrent. The reliability of data was fulfilled by following Lincoln and Guba criteria. We stopped data collection when no new concept was added and data saturation was achieved. Based on the experience of elders, we identified three categories: 1) Self-transcendence, 2) Social transcendence, and 3) Cosmic level. These portrayed gerotranscendence as a continuous process confronting age-related change. The finding suggests that gerotranscendence was introduced as a dynamic process that occurred simultaneously with active aging accompanying the journey of life.